Investigating the Frequency of Ventriculoperitoneal Shunt Requirement in Patients Diagnosed with Normal Pressure Hydrocephalus - Man, Raza; Mehmood, Khalid; Ullah, Kiramat; Saqib, Muhammad; Nawaz, Shahid; Ullah, Fareed (Journal of Neonatal Surgery, 2025)
Background: Normal Pressure Hydrocephalus (NPH) is a neurological condition that is distinguished by the abnormal accumulation of cerebrospinal fluid. This condition is especially prevalent in the geriatric population and is associated with cognitive decline, urinary incontinence and gait problems. Objective: To determine the frequency of ventriculoperitoneal (VP) shunt requirement in patients diagnosed with NPH and to identify clinical, radiological and procedural factors that are predictive of successful shunt intervention. Methods: A cross-sectional investigation was conducted on 45 patients who were diagnosed with NPH. The clinical data, which encompassed symptomatology and response to acetazolamide (AZM) and lumbar puncture (LP), were analyzed. The hippocampal atrophy, ventricular size (Evans' Index) and other pertinent markers were the primary focus of radiological assessments. The predictors of VP shunt requirement and post-shunt symptom improvement were identified using logistic regression. Results: Insufficient improvement with LP and AZM required the implantation of a VP shunt in 22.2% (n=10) of the 45 patients. Increased ventricular size (Evans' Index; OR = 2.85, p<0.05) and hippocampal atrophy (OR = 3.46, p<0.05) were significant predictors of shunt requirement. Patients who did not exhibit symptom improvement following LP or AZM were considerably more likely to require shunt surgery (p<0.01). Infection (10%) and malfunction (20%) were among the complications that affected 30% of patients who underwent shunt treatment. Conclusion: The necessity of a VP shunt in NPH patients is significantly predicted by increased ventricular size and hippocampal atrophy. The necessity of shunting is firmly suggested by the absence of symptom improvement following LP and AZM. VP shunting continues to be the most effective treatment for symptom relief in appropriately selected NPH patients, despite the associated hazards.